Bhumsa wrote:

Please explain why C? I chose D.

(n-3)^2 = 4m^2

Moving RHS to LHS and using a^2 -b^2 = (a+b)(a-b)

We get

N-3-2m =0 and n- 3+2m =0

Therefore

N=2m+3 and N = 3-2m

Therefore the question is statistfied.

Similarly for statement B.

Therefore answer should be D

You're correct to say that statement 1 yields 2 possible solutions (in red above)

However, if N = 2m + 3, then the answer to the target question is "YES, n does equal 2m + 3)

And if N = 3 - 2m , then the answer to the target question is "NO, n does not equal 2m + 3)

Since we have 2 DIFFERENT answers to the target question, the statement is NOT sufficient.

_________________

Test confidently with gmatprepnow.com